Media Pembelajaran: Jenis dan Teknik Pemilihan dalam Pembelajaran PAI - Kafa, Choiri (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2024)
The aim of this research is to identify the various types and techniques for selecting media in Islamic Religious Education (PAI) and to formulate recommendations or strategies for optimizing media in the context of religious education. Through this research, it is expected to clearly illustrate to what extent the types and characteristics of media, as well as their effectiveness in PAI learning, can significantly contribute to students' understanding of religious teachings and stimulate their interest and engagement in the learning process. Using a qualitative literature review method, this study aims to summarize and analyze a variety of media that can be used in Islamic Religious Education. This approach will yield a wide range of media that can be employed and techniques for selecting appropriate instructional media to facilitate the comprehension of religious concepts, student engagement, and the appreciation of spiritual values in PAI learning. This article will discuss various types of instructional media that can be utilized in PAI education, such as textbooks, interactive multimedia, instructional videos, and others. Additionally, it will also examine various effective media selection techniques in the context of PAI education, including considerations based on learning objectives, student characteristics, and relevant pedagogical aspects. Knowledge about the types of media and appropriate selection techniques will assist PAI educators in improving the quality of teaching and facilitating students' understanding of Islamic values.